Unsteady MHD thermal diffusive and radiative fluid flow past a vertical porous plate with chemical reaction in slip flow regime - Kumar, D. Ravi; Reddy, K. Jayarami; Raju, M. Changal (Zielona Góra: Uniwersytet Zielonogórski)
An analytical solution of an MHD free convective thermal diffusive flow of a viscous, incompressible, electrically conducting and heat-absorbing fluid past a infinite vertical permeable porous plate in the presence of radiation and chemical reaction is presented. The flow is considered under the influence of a magnetic field applied normal to the flow.
Keywords: MHD; free convection; heat transfer; mass transfer; slip flow regime; thermal diffusion; radiation reaction; chemical reaction